2010
DOI: 10.1111/j.1365-2141.2010.08129.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring heparin anticoagulation in the acute phase response

Abstract: Summary The anticoagulant effect of unfractionated heparin (UFH) is monitored using the activated partial thromboplastin time (APTT). An APTT of 1·5–2·5 times the control is usually taken as the therapeutic range and assumed to reflect an anti‐activated factor X (anti‐Xa) level of 0·35–0·7 u/ml. However, in some cases, despite administration of sufficient heparin to achieve a therapeutic anti‐Xa assay level, the APTT remains sub‐therapeutic. This ‘apparent heparin resistance’ is commonly due to high levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 16 publications
0
36
1
1
Order By: Relevance
“…Apparent heparin resistance is an inadequate aPTT response in vitro despite appropriate in vivo antithrombotic efficacy of heparin as measured by anti-Xa levels. 4 To our knowledge, this is the first report of apparent argatroban resistance associated with elevated factor VIII levels. A recent report described a patient who received argatroban doses up to 15.5 µg/kg/min to achieve the desired aPTT.…”
Section: Discussionmentioning
confidence: 92%
“…Apparent heparin resistance is an inadequate aPTT response in vitro despite appropriate in vivo antithrombotic efficacy of heparin as measured by anti-Xa levels. 4 To our knowledge, this is the first report of apparent argatroban resistance associated with elevated factor VIII levels. A recent report described a patient who received argatroban doses up to 15.5 µg/kg/min to achieve the desired aPTT.…”
Section: Discussionmentioning
confidence: 92%
“…For example, a patient with factor XII deficiency may have a prolonged aPTT, however will not have an increased risk of bleeding, whereas a patient with factor VIII deficiency and a similarly prolonged aPTT will have a high risk of bleeding. Patients with acute inflammatory states may also manifest heparin resistance [14, 22, 23].…”
Section: Monitoring Of Heparinmentioning
confidence: 99%
“…On the other hand, using thromboelastography and thrombin generation, Uprichard et al . have recently shown that aPTT may be a more accurate measure of anticoagulant effect of UFH in vivo than anti‐Xa assay [13]. Whereas monitoring of LMWHs is not required routinely, anti‐Xa assay, rather than aPTT, may be useful for optimizing dose in certain groups of patients such as the elderly, pregnant and in renal failure [14].…”
Section: Biologic Activity Monitoring and Interactions Of Conventionmentioning
confidence: 99%